Case Report: Chronic Embolic Stroke With Bronchopneumonia In Geriatric Patients - Johanes Andrew; Dana Profit Sampurno; Rayhan Al-ghifari Iridansyah Siregar; Eric Eric (Cerdika: Jurnal Ilmiah Indonesia, 2025)
Stroke is a neurological deficit of the central nervous system caused by vascular issues, affecting around 800,000 individuals annually. According to Riskesdas 2018, the prevalence of stroke is approximately 10.9%, with the highest rates in East Kalimantan and the lowest in Papua. In this study, we present a case of a 79-year-old male diagnosed with embolic stroke at Royal Taruma Hospital. The patient was admitted with a fever that persisted for four days prior to hospitalization. Comprehensive anamnesis, physical examination, and diagnostic tests confirmed a diagnosis of febris e.c. bronchopneumonia and hemiparesis duplex e.c. chronic CVDNH. Embolic strokes occur when a cerebral artery is occluded by a clot originating from the heart, aortic arch, or a major cerebral artery, often leading to maximal neurological deficits at the onset. This case underscores several risk factors for embolic stroke, including hypertension, dyslipidemia, and advanced age. The patient was treated with rivaroxaban (10 mg once daily) for anticoagulation and meropenem (1 g three times daily) to manage the infection. Post-treatment, a comprehensive geriatric assessment revealed no signs of urinary or fecal incontinence, and the patient did not exhibit polypharmacy. Following intervention, there was a notable improvement in neurological function and resolution of infectious symptoms. This case highlights effective management strategies for a 79-year-old male with complex medical conditions and emphasizes the necessity of timely interventions in elderly patients for better prognostic outcomes.